2014
DOI: 10.1016/j.dsr2.2013.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and toxicity of the diatom Pseudo-nitzschia Peragallo in the Gulf of Maine, Northwestern Atlantic Ocean

Abstract: Multiple species in the toxic marine diatom genus Pseudo-nitzschia have been identified in the Northwestern Atlantic region encompassing the Gulf of Maine (GOM), including the Bay of Fundy (BOF). To gain further knowledge of the taxonomic composition and toxicity of species in this region, Pseudo-nitzschia isolates (n=146) were isolated from samples collected during research cruises that provided broad spatial coverage across the GOM and the southern New England shelf, herein referred to as the GOM region, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 90 publications
(194 reference statements)
4
40
1
Order By: Relevance
“…To date, 17 species of Pseudo-nitzschia have been shown to be toxigenic [5,8,19,20]. In this study, LC-MS/ MS analysis confirmed the presence of DA in cultured P. fukuyoi from Vietnamese waters.…”
Section: Discussionsupporting
confidence: 83%
“…To date, 17 species of Pseudo-nitzschia have been shown to be toxigenic [5,8,19,20]. In this study, LC-MS/ MS analysis confirmed the presence of DA in cultured P. fukuyoi from Vietnamese waters.…”
Section: Discussionsupporting
confidence: 83%
“…Its transapical axis is narrower (2.6–4.2 μm) compared to P. fraudulenta (Cleve) Hasle and P. subfraudulenta (both >4.1 μm; Moschandreou and Nikolaidis , Fernandes et al. , this study).…”
Section: Resultsmentioning
confidence: 43%
“…Pseudo-nitzschia australis or P. cuspidata typically dominate toxic Pseudo-nitzschia blooms in Puget Sound and WA coastal waters (Trainer et al 2007), although regional isolates of P. multiseries produce high DA levels in culture (Guannel et al 2011) and P. seriata isolates elsewhere are toxic (Fehling et al 2004, Fernandes et al 2014). Our cruise samples from June 2006 were collected nine months after separate toxic blooms of P. cuspidata and P. australis in Puget Sound resulted in shellfish harvest closures (Trainer et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Interest in Pseudo-nitzschia taxonomy and ecology has increased over the past few decades largely because at least 14 species are capable of producing the neurotoxin, domoic acid (DA). Toxin production among these species varies over ~9 orders of magnitude (Trainer et al 2012, Fernandes et al 2014). DA accumulates in filter feeding shellfish and planktivorous fish and can cause Domoic Acid Poisoning in marine vertebrates that feed on contaminated prey (Lefebvre et al 2010).…”
Section: Introductionmentioning
confidence: 99%